Butler to the world how Britain became the servant of tycoons, tax dodgers, kleptocrats and criminals - Oliver, Bullough (London Profile Books, 2022)
The Suez Crisis of 1956 was Britain's 20th-century nadir, the moment when the once superpower was bullied into retreat. In the immortal words of former US Secretary of State Dean Acheson, 'Britain has lost an empire and not yet found a role.' But the funny thing was, Britain had already found a role. It even had the costume. The leaders of the world just hadn't noticed it yet.
Includes index
Keywords: Wealth -- Moral and ethical aspects -- Great Britain; Business ethics -- Great Britain; Great Britain -- Economic conditions; Great Britain -- Economic conditions -- Moral and ethical aspects